Azygous Anterior Cerebral Artery Acute Occlusion Managed With Endovascular Mechanical Thrombectomy: 2-Dimensional Operative Video. Issue 4 (27th July 2018) - Rangel-Castilla, Leonardo; Siddiqui, Adnan H
Abstract: Mechanical thrombectomy has become the standard of care for management of most acute large-vessel occlusion (LVO) strokes. Most intracranial occlusions are located in the middle cerebral and internal carotid arteries. We present a unique case of acute occlusion of an azygous anterior cerebral artery (ACA). A 59-yr-old man with known hypertension and alcoholism presented with right hemiparesis, right facial palsy, aphasia, and dysarthria. His initial National Institutes of Health Stroke Scale (NIHSS) score was 20. Computed tomographic angiography and perfusion imaging demonstrated acute bilateral ACA occlusion with viable penumbra and preserved cerebral blood volume. The patient was not a candidate for intravenous tissue plasminogen activator because he presented with a wake-up stroke. After consent was obtained from his family, the patient was taken urgently for endovascular recanalization. Digital subtraction angiography confirmed acute azygous ACA occlusion. Under conscious sedation, the patient underwent mechanical thrombectomy with a stent retriever and a large-bore aspiration catheter. Successful revascularization (thrombolysis in cerebral infarction [TICI] grade 3) of the azygous ACA and both A2 arteries was obtained after 2 attempts and the use of a different stent retriever (first a 3 × 30 mm Trevo [Stryker Neurovascular, Kalamazoo, Michigan] and then a 4 × 40 mm Solitaire Platinum [Medtronic, Dublin, Ireland]). A reperfusion catheter was used during both attempts. No procedure-related complications occurred. The patient was discharged to a rehabilitation facility 3 d after the procedure with an NIHSS score of 2. In this video, we present the operative nuances of an uncommon location of LVO and its endovascular management.